Shear Bond Strength of Composite to Dentin following Light Curing with Light Emitting Diode and Quartz Tungsten Halogen Light Curing Units - Mansoreh Mirzaee; Esmaeil Yassini; Mohammad Javad Kharazifard; Mehrnaz Vaziri (Islamic Dental Association of Iran, 2015)
Background and Aim: The use of light emitting diode (LED) light curing units has recently increased due to optimal properties such as longer durability, no need for filter and less heat generation compared to quartz tungsten halogen (QTH) devices. The aim of this study was to assess the shear bond strength of composite to dentin following lightcuring with QTH and LED light curing units for different time periods. Materials and Methods: In this experimental study, 60 sound extracted human molar and premolar teeth with no decay or restorations were collected. The buccal surface of the teeth was ground to expose adequate amount of dentin. The teeth were randomly divided into six groups. After acid etching and bonding, composite was packed in plastic cylindrical molds and placed on dentin surface. Groups one, two and three were cured by a LED unit (Wood Pecker) with ramp method for 20, 30 and 40 seconds, respectively. Groups four, five and six were cured with a QTH unit (Optilux 501) with a light intensity of 500 mW/cm2 for 20, 30 and 40 seconds, respectively. After keeping the samples for two weeks in distilled water at room temperature, shear bond strength was measured by a universal testing machine at a crosshead speed of 1mm/minute. The data were analyzed by Two-way ANOVA, one-way ANOVA and Tukey's HSD test. Results: One-way ANOVA showed a significant difference among the groups and the mean shear bond strength was the highest following light curing by LED device for 40 seconds (18.63 MPa). Pairwise comparisons by Tukey's test showed significant differences in shear bond strength of groups cured with LED unit (P= 0.059 for the difference between 20 seconds and 40 seconds and P=0.004 for the difference between 30 seconds and 40 seconds). Conclusion: Use of LED units (ramp method) yielded superior results in terms of shear bond strength compared to QTH. Also, 40 seconds of curing is recommended in use of LED devices.